Partisipasi Perempuan dalam Aktivitas Ekonomi Lokal Berbasis Tanaman Pangan - Wahyudi David; Sirin Fairus; Kadek Juli Ardani; Syifa Azzahra (LPkM Universitas Bakrie, 2026)
This initiative aligns with Sustainable Development Goal 5, which aims to achieve gender equality and empower all women. Recognizing gender equality as a fundamental human right and a cornerstone for sustainable development, Koperasi Serba Usaha Lestari plays a strategic role in empowering women through local food crop management. The program seeks to enhance the competitiveness of local food products by involving 45 female group members in community-based activities. The methodology consists of three main stages: conceptual education, practical mentoring, and evaluation, tailored to each training theme. The three training modules include packaging design and techniques, business feasibility studies, and capacity building through organic waste utilization. The program resulted in a knowledge increase among more than 65% of participants, with the acquired skills expected to be applied within their groups to support local economic development and women's empowerment.